1993
DOI: 10.1099/00221287-139-12-2973
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-dependent growth of an FK506- and CsA-hypersensitive mutant of Saccharomyces cerevisiae

Abstract: The immunosuppressants FK506 and cyclosporin A (CsA) bound to their receptors, FKBP12 or cyclophilin, inhibit the Ca2+/calmodulin-dependent protein phosphatase, calcineurin, preventing T cell activation or, in yeast, recovery from a-mating factor arrest. Vegetative growth of yeast does not require calcineurin, and in strains sensitive to FK506 or CsA, growth is inhibited by concentrations of drug much higher than those required to inhibit T cell activation or recovery from mating factor arrest. We now describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…FK506 was added to one portion at a final concentration of 1 g/ml. Previous work has shown that the growth of wild-type cells is unaffected by this concentration of FK506, while the growth of the fks1 mutant strain is eventually inhibited (62). Logarithmic growth continued for 2 h after the addition of drug, at which time samples were removed for the isolation of total RNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FK506 was added to one portion at a final concentration of 1 g/ml. Previous work has shown that the growth of wild-type cells is unaffected by this concentration of FK506, while the growth of the fks1 mutant strain is eventually inhibited (62). Logarithmic growth continued for 2 h after the addition of drug, at which time samples were removed for the isolation of total RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that null mutations in FKS1 result in FK506-hypersensitive and Ca 2ϩ -responsive growth (18,21,62). FK506 is a potent inhibitor of the Ca 2ϩ /calmodulin-dependent phosphoprotein phosphatase calcineurin (62).…”
Section: Resultsmentioning
confidence: 99%
“…Yeast calcineurin is inhibited by the immunosuppressant components FK506 and CsA [52]. Recently, an FK506-and CsA-hypersensitive mutant 0rksl) was isolated, which was synthetically lethal with calcineurin mutants [53]. Cloning of FKS1 showed that the gene was identical to CWH53 (F. Foor, pers.…”
Section: Discussionmentioning
confidence: 99%
“…These preparations were enriched in the product of the FKS1 gene, which, together with its homologue, FKS2 (126), has been implicated in the activity of glucan synthase (127,128). Mutants in FKS1 were first isolated in a screen for hypersensitivity to immunosuppressants (129), and again, under the name etg1, in a screen for strains resistant to glucan synthase inhibitors (127). Null ( f ks1 ) mutants show a decrease in glucan synthase activity (128) and in incorporation of glucose into β (1 → 3)glucan in vivo (130); double null ( f ks1 f ks2 ) mutants are inviable (126).…”
Section: On the Nature Of The Direct Target Of Rho1 In The Glucan Synmentioning
confidence: 99%